Automation design for monorail-based system processes - Besa, B.; Chanda, K.; Kuruppu, Mahinda (2016)
Currently, conventional methods of decline development put enormous cost pressure on the profitability of mining operations. This is the case with narrow vein ore bodies where current methods and mine design of decline development may be too expensive to support economic extraction of the ore. According to studies, the time it takes to drill, clean and blast an end in conventional decline development can be up to 224 minutes. This is because once an end is blasted, cleaning should first be completed before drilling can commence, resulting in low advance rates per shift. Improvements in advance rates during decline development can be achieved by application of the Electric Monorail Transport System (EMTS) based drilling system. The system consists of the drilling and loading components that use monorail technology to drill and clean the face during decline development. The two systems work simultaneously at the face in such a way that as the top part of the face is being drilled the pneumatic loading system cleans the face. However, to improve the efficiency of the two systems, critical processes performed by the two systems during mining operations must be automated. Automation increases safety and productivity, reduces operator fatigue and also reduces the labour costs of the system. The aim of this paper is, therefore, to describe automation designs of the two processes performed by the monorail drilling and loading systems during operations. During automation design, critical processes performed by the two systems and control requirements necessary to allow the two systems execute such processes automatically have also been identified.